2021
DOI: 10.3389/fmed.2021.745789
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation and Its Impact on the Pathogenesis of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The clinical manifestations of COVID-19 include dry cough, difficult breathing, fever, fatigue, and may lead to pneumonia and respiratory failure. There are significant gaps in the current understanding of whether SARS-CoV-2 attacks the CNS directly or through activation of the peripheral immune system and immune cell infiltration. Although the modality of neurological impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 194 publications
0
59
0
Order By: Relevance
“…SARS-CoV-2 is an enveloped, single-stranded RNA virus, belonging to the Coronaviridae family [ 65 ]. Neurological symptoms and sequelae, during or after SARS-CoV-2 infection, have been reported [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 is an enveloped, single-stranded RNA virus, belonging to the Coronaviridae family [ 65 ]. Neurological symptoms and sequelae, during or after SARS-CoV-2 infection, have been reported [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neurological symptoms and sequelae, during or after SARS-CoV-2 infection, have been reported [ 66 , 67 ]. Whether SARS-CoV-2 infection causes these complications through direct infection of the CNS or via a SARS-CoV-2-induced immune response is still unclear [ 65 , 68 ]. To investigate if the CNS is susceptible to direct infection, 8 out of 11 studies on SARS-CoV-2 (73%) reported on SARS-CoV-2 receptor expression in the CNS ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One hypothesis for the brain alteration in SARS-CoV-2 infection is a neuroinflammatory response (6). Our results confirmed a significant association between (i) a decreased GMV and Th in frontal, fronto-orbital, and temporal regions and (ii) increased CSF levels of indirect inflammatory markers (protein, blood/albumin ratio, and EN-RAGE).…”
Section: Discussionmentioning
confidence: 99%
“…Following administration of the BNT162b2, an mRNA vaccine encoding a P2 mutant spike protein (PS 2) derived from the SARS-CoV-2 spike (S) glycoprotein, the genetic material is expressed, which stimulates an immune response which is very similar to post-viral status, with robust release of immune-modulatory cytokines such as IFNγ, IL-2 and IL-12p70, 5 but also downregulation of TJ proteins as well as increasing some cytokines level, including TNFα, IL-6 and IL-10. 6 TNFα has neurotoxic effects mediated by a rapid impairment of mitochondrial function, 7 while IL-2 and IL-6 could play a neurotoxic role, sometimes associated with demyelinating neuropathies. 8,9 The cytokines activated by SARS-Cov2 protein fragments could also trigger vasculitis in and around nerves.…”
mentioning
confidence: 99%
“…8,9 The cytokines activated by SARS-Cov2 protein fragments could also trigger vasculitis in and around nerves. 6 Molecular mimicry through cross-reactivity between epitopes within the COVID-19 spike-bearing gangliosides and some gangliosides containing a disialosyl moiety (GD1b, GQ1b and GT1b) was proposed in patients with neuropathies after COVID-19. 10 Although all these proposed mechanisms could play a role in post-COVID-19 and post-COVID-19 vaccination associated cranial (and peripheral) neuropathies, the relationship remains of probability, especially when there is a plausible timeframe between exposure and clinical event and no other causes were found, but overall these very rare instances do not diminish at all the overwhelming positive benefit-risk ratio of COVID-19 vaccines.…”
mentioning
confidence: 99%